2017
DOI: 10.1302/2046-3758.64.2000470
|View full text |Cite
|
Sign up to set email alerts
|

Externalised locking compression plate as an alternative to the unilateral external fixator: a biomechanical comparative study of axial and torsional stiffness

Abstract: ObjectivesExternal fixators are the traditional fixation method of choice for contaminated open fractures. However, patient acceptance is low due to the high profile and therefore physical burden of the constructs. An externalised locking compression plate is a low profile alternative. However, the biomechanical differences have not been assessed. The objective of this study was to evaluate the axial and torsional stiffness of the externalised titanium locking compression plate (ET-LCP), the externalised stain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 43 publications
0
41
0
Order By: Relevance
“…(P= 0.171). However, there was a significant difference in mean torsional between LCP (stainless steel) (0.639 N/mm) (0.686 Nm/degree) LCP (titanium) and EF (0.512 Nm/degree) (P=0.013) [4] . That study used 15 synthetic tibias bone model and standard AO technique for the fixation of construct.…”
Section: Biomechanical Studiesmentioning
confidence: 87%
See 1 more Smart Citation
“…(P= 0.171). However, there was a significant difference in mean torsional between LCP (stainless steel) (0.639 N/mm) (0.686 Nm/degree) LCP (titanium) and EF (0.512 Nm/degree) (P=0.013) [4] . That study used 15 synthetic tibias bone model and standard AO technique for the fixation of construct.…”
Section: Biomechanical Studiesmentioning
confidence: 87%
“…In the early years, the aim of plate fixation outside the skin was to reduce the stress on bone and periosteum. In 1987, there was one biomechanical study regarding external plate fixation using Zesopl osteosynthesis system [4][5] . This initial study was not to use alternative to the traditional external fixator in the management of open fracture but to replace the compression plate in the treatment of closed fractures.…”
Section: Introductionmentioning
confidence: 99%
“…In the technique “supercutaneous plating” by Kloen, the LCP can be used as an external fixator for treatment of distal tibial fractures and humeral infected nonunion. In a biomechanical comparative study of axial and torsional stiffness by Ang et al ,. LCP was used as an external fixator in comparison with UEF.…”
Section: Discussionmentioning
confidence: 99%
“…It seems an attractive technique to deal with fractures involving complex wounds or to improve the tolerability of treatment. It has been reported that externalized LCP could act an alternative to the unilateral external fixator (UEF) for treating distal tibial fractures, and the axial and torsional stiffness are not compromised. Although this new technique still has some deficiencies, such as potential screw channel infections and inconvenience for nurses, it provides us with a new concept for clinical treatment of distal‐third diaphyseal humerus fractures.…”
Section: Introductionmentioning
confidence: 99%
“…The stiffness of external fixators reported in previous literatures has ranged from 50 N/mm to 2500 N/mm in axial compression, 10 Nm/deg to 100 Nm/deg in four-point bending, and 1 Nm/deg to 4 Nm/deg in torsion, respectively (4,6,(28)(29)(30)(31). The stiffness values of all of the bone-implant constructs in our study research were within these ranges, and the plate-type external fixator provided remarkably higher torsional stiffness than the UEF.…”
Section: Construct Stiffnessmentioning
confidence: 99%